Android-Based Interactive Learning Media In Mathematics Learning - Nuthfah Faijah; Wahyu Setyaningrum (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
The learning process is highly dependent on the interaction between educators and learners. To enhance learning effectiveness, innovation in instructional media that can stimulate students’ learning interest is essential. One such innovation is the development of interactive Android-based learning media. This study aims to develop an interactive Android-based learning medium using the iSpring Suite application for seventh-grade algebra instruction and to analyze its feasibility. This research employed a development research approach using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. Both quantitative and qualitative data analysis techniques were applied. The developed media were validated by subject-matter experts and media experts and were subsequently tested on 65 students. The validation results indicate that the learning media fall into the “highly feasible” category based on expert evaluations and student responses. A total of 97% of students rated the media as highly suitable for use in learning activities. The strengths of the developed media include the variety of question types (multiple choice, true or false, drag and drop, and short answer) as well as reflective features that enable students to evaluate their own understanding. This study demonstrates that interactive, flexible, and contextual Android-based learning media can effectively enhance students’ learning interest and conceptual understanding in mathematics. These findings contribute to the advancement of technology-based learning that aligns with the principles of the Kurikulum Merdeka and the demands of 21st-century education.